2010
DOI: 10.1152/ajpcell.00496.2009
|View full text |Cite
|
Sign up to set email alerts
|

Laminin regulates mouse embryonic stem cell migration: involvement of Epac1/Rap1 and Rac1/cdc42

Abstract: Suh HN, Han HJ. Laminin regulates mouse embryonic stem cell migration: involvement of Epac1/Rap1 and Rac1/cdc42. Am J Physiol Cell Physiol 298: C1159 -C1169, 2010. First published January 20, 2010 doi:10.1152/ajpcell.00496.2009Laminin is the first extracellular matrix (ECM) component to be expressed in the developing mammalian embryo. However, the roles of laminin or the related signal pathways are not well known in mouse embryonic stem cells (mESCs). Presently, we examined the effect of laminin on mESC migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 65 publications
(50 reference statements)
4
26
0
Order By: Relevance
“…RAP1A, and the highly related protein RAP1B (95% amino acid identity), belong to the Ras family of small GTPases, regulating various cellular processes such as cell adhesion and migration (14)(15)(16); studies in Xenopus and zebrafish have shown that rap1a and rap1b morphants exhibit similar gastrulation defects, highlighting the important role of both proteins in early development (17). RAP1 is known to exert opposing effects on the MAPK pathway (18), depending on tissue-and cell-specific context: an activating effect through BRAF (19,20) and a repressive effect through RAF1 (21).…”
Section: Resultsmentioning
confidence: 99%
“…RAP1A, and the highly related protein RAP1B (95% amino acid identity), belong to the Ras family of small GTPases, regulating various cellular processes such as cell adhesion and migration (14)(15)(16); studies in Xenopus and zebrafish have shown that rap1a and rap1b morphants exhibit similar gastrulation defects, highlighting the important role of both proteins in early development (17). RAP1 is known to exert opposing effects on the MAPK pathway (18), depending on tissue-and cell-specific context: an activating effect through BRAF (19,20) and a repressive effect through RAF1 (21).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in keratinocytes, laminin-integrin interactions result in keratinocyte polarization, lamellipodia extension and induction of migration (Choma et al, 2007). Similarly, laminin-integrin interactions regulate embryonic stem cell migration (Suh and Han, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, deletion of laminin genes disrupts the formation of the retinal inner limiting membrane (ILM) (Pinzón-Duarte et al, 2010;Edwards et al, 2010). As laminins and their receptors regulate cell migration (Suh and Han, 2010;Fujiwara et al, 2004;Desban et al, 2006;Echtermeyer et al, 1996), including brain astrocytes in vitro (Armstrong et al, 1990), we hypothesize that laminins regulate both astrocyte migration and spatial organization in the retina.…”
Section: Introductionmentioning
confidence: 99%
“…The Epac effector Rap2 is involved in Wnt/b-catenin signaling by stabilizing b-catenin (Choi and Han, 2005) and could in this contribute to fibrotic processes. Epac strengthens tethering of catenin to adherens junctions and tight junctions (Netherton et al, 2007;Raymond et al, 2007;Noda et al, 2010;Rampersad et al, 2010;Suh and Han, 2010). Intriguingly, the secreted lysophospholipase D autotaxin promotes cancer invasion through a cAMP-Epac-Rac1 pathway in response to lysophosphatidic acid receptor 4 stimulation, a process supported by blood vessel formation through autotaxin (van Meeteren et al, 2006;Harper et al, 2010).…”
Section: Biology Of the Epac Signalosomementioning
confidence: 99%
“…Notably, Epac1 modulates the endothelial barrier independent from the Rho GTPases and Rap (see below). As Rap1 promotes cell-cell junction formation through signaling to E-cadherin-catenin and integrin-extracellular matrix complexes (Retta et al, 2006;Pannekoek et al, 2009;Noda et al, 2010;Suh and Han, 2010; Fig. 7), reduction of endothelial permeability through Rap1 activation by Epac1 most likely reflects its signaling property to the actin-microtubule network.…”
Section: Epac and The Vasculature 1 Epac And The Endothelial Barrmentioning
confidence: 99%